KEAMANAN ENDPOINT API MENGGUNAKAN OAUTH2 PADA UNIT LAYANAN TERPADU UNIVERSITAS MALIKUSSALEH: APPLICATION PROGRAMMING INTERFACE (API) SECURITY AT THE INTEGRATED SERVICE UNIT OF MALIKUSSALEH UNIVERSITY - Gilang Ramadhan Purba; Rizal; Yesy Afrillia (LPPM Universitas Abdurrab, 2025)
Malikussaleh University, as a higher education institution, strives to improve service quality through its Integrated Service Unit (ULT). However, monolithic systems often become an obstacle due to their rigidity and difficulty in development. This research aims to design and build an efficient and secure ULT system model by adopting a microservice architecture. The methodology includes designing the microservice architecture, developing APIs, and implementing security using Laravel Passport, which supports the OAuth2 standard to protect Machine-to-Machine (M2M) communication. Each service, such as administration, academic, and personnel services, is broken down into independent services packaged in Docker containers. The results show the successful implementation of a system prototype where each service can communicate securely via API. Testing proved that the token-based and scope-based authentication and authorization mechanisms successfully protected endpoints from unauthorized access. Thus, the implemented microservice architecture model and API security are proven to be a solution for a modular, secure, and efficient service digitalization in the university environment.